2022
DOI: 10.3390/ijerph19042192
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Impacts of the COVID-19 Pandemic on Food Behaviors in North Africa: Cases of Egypt, Morocco, and Tunisia

Abstract: The COVID-19 pandemic-related measures in the Near East and North Africa (NENA) region have resulted in many lifestyle modifications, including changes in diet and food buying patterns among adults. However, the pandemic has impacted women and men differently and exacerbated existing socio-economic and gender inequalities. Indeed, numerous studies conducted worldwide have shown that the COVID-19 pandemic had a disproportionately negative impact on women compared to males. Therefore, this paper aims to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…As demonstrated in COVID-19 specific studies related to dietary habits, Hassen and colleagues demonstrated that females ( n = 511) and males ( n = 484) had different consumption patterns dependent on the country of residence. For example, in Morocco, females consumed more food due to fear, stress, and anxiety over COVID-19 compared to males, but in Egypt, males consumed more comfort food than females [ 40 ]. Another study that focused on 3 European countries–Denmark, Germany, and Slovenia, of a total of 2680 adults, showed that there were differences in consumption habits of males and females of foods/beverages that increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in COVID-19 specific studies related to dietary habits, Hassen and colleagues demonstrated that females ( n = 511) and males ( n = 484) had different consumption patterns dependent on the country of residence. For example, in Morocco, females consumed more food due to fear, stress, and anxiety over COVID-19 compared to males, but in Egypt, males consumed more comfort food than females [ 40 ]. Another study that focused on 3 European countries–Denmark, Germany, and Slovenia, of a total of 2680 adults, showed that there were differences in consumption habits of males and females of foods/beverages that increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed and adapted based on previous studies on the impact of the COVID-19 pandemic on food-related activities, including food waste performed in the MENA (Middle East North Africa) region ( Ben Hassen et al., 2021e ; Ben Hassen et al., 2022a , Ben Hassen et al., 2022b ; El Bilali et al., 2021a ), and the Balkans ( Ben Hassen et al., 2021b , Ben Hassen et al., 2021c ; Berjan et al., 2021 ). For the Iranian context, the questionnaire was translated into Persian.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that women and children are disproportionately impacted during economic crises, especially when it comes to food security and nutrition [ 41 ]. Often, women and girls are vulnerable on all dimensions of food security, and they suffer nutrient deficiencies.…”
Section: Covid-19 Pandemic Lockdown and The Health And Economic Impac...mentioning
confidence: 99%